Classification decisions taken by the Harmonized System Committee from the 27th to 46th sessions (2001 - 2010) (The Organization BrusselsBE, 2011)
Consists of the summary of decisions taken by the Harmonized System (HS) Committee in cases where classification decisions have been taken without reference to specific headings (no. 1 to no. 5)and, in cases where classification decisions have been taken with reference to specific headings (no. 6 to no. 259).
On permanent loan to Single Market and Economy Sub-Programme (Mr. Breedy, Mr. Black, Mr. Watson).